Principal component thermography for flaw contrast enhancement and flaw depth characterisation in composite structures - Rajic, N (Composite structures, 2002)
This study reports on the application of principal component thermography to the nondestructive inspection of composite structures. The technique is based on a singular value decomposition of the measured response to pulsed thermal excitation as applied in the course of a normal flash thermographic inspection. Trials on synthetically generated data show evidence of excellent noise-rejection qualities which manifest high levels of flaw contrast relative to that present in the unprocessed data. A simple analytical expression is then derived that relates a characteristic time furnished by the decomposition to the flaw depth, providing a basis for flaw depth estimation. This framework is shown to provide flaw-depth estimates with good levels of precision and robustness. Finally, application to experimental data is considered. An AS4/3501 composite laminate sample containing an assortment of teflon inserts is subject to active thermographic inspection and the response data analysed using the proposed approach. The results conclusively demonstrate the practical efficacy of the approach, and confirm the attractive properties outlined in relation to the numerical tests.